Intravenous thrombolysis in ischemic stroke patients based on non-contrast CT in the extended time-window - Emde, Julia; Baumgart, Romy; Langguth, Niklas; Juenemann, Martin; Gerner, Stefan T. (Frontiers in Stroke, 2022)
Recent trials provided evidence for safety and efficacy of intravenous thrombolytic therapy(IVT) in ischemic stroke patients beyond the 4.5h time-window if ischemic penumbra is present in multimodal imaging. But, advanced imaging by either MRI or CT-Perfusion is not available 24/7 at most stroke-centers. Therefore, the current review addresses the use of non-contrast CT(NCCT) to identify ischemic stroke patients suitable for IVT in the unknown or extended time-window in terms of efficacy and safety. The current data on NCCT based IVT-strategies in ischemic stroke patients presenting in the unknown or late time-window are relatively scarce and mainly provided by small retrospective samples. One larger registry(TRUST-CT) underlines the safety and efficacy of IVT without advanced imaging with more IVT-patients reaching an excellent outcome compared to the non-IVT treated control group. Current meta-analysis provides evidence that the rate of symptomatic intracerebral hemorrhage(sICH) is similar in the wake-up and unknown onset time-window compared to the 4.5h time-window if patients are selected by NCCT. Results of the upcoming TWIST-trial investigating Tenecteplase(TNK) for NCCT-based IVT revealed no signals regarding an increased rate of sICH, however there was no benefit regarding functional outcomes. So far, it is not well established whether advanced imaging is indispensable and NCCT could be sufficient to identify stroke patients in the extended window who benefit of IVT-treatment. However, current data suggests the safety of NCCT-based IVT in the extended time-window. Therefore unavailable advanced neuroimaging should not cause delay, or even exclusion of patients from IVT and other recanalizing therapies per se.